Biochar effects on phosphorus availability in agricultural soils: A meta-analysis - Glaser, Bruno; Lehr, Verena-Isabell (Scientific reports, 2019)
Phosphorus (P) is a limiting nutrient for plants and an essential element for all life on Earth. As the resources of phosphate rock are depleting, new management tools for environmentally friendly P fertilizers are needed. In order to achieve this, recent studies have proposed to use biochar, a carbon-rich solid product of thermochemical conversion of biomass with minimal or zero oxygen supply, as slow-release P fertilizer. However, the effects of biochar on plant-available P in soils have been reported to be variable. Therefore, we quantitatively evaluated existing peer-reviewed data using meta-analysis to draw general conclusions. In the present study, we evaluated 108 pairwise comparisons to their response of biochar application on P availability in soils. Our results indicate that biochar can act as a short-, mid-, and long-term P fertilizer with its effect depending on feedstock, pyrolysis temperature and application amount. Overall, the addition of biochar significantly increased the P availability in agricultural soil by a factor of 4.6 (95% confidence interval 3.4–5.9), independent of the used feedstock for biochar production. Only biochar application amounts above 10 Mg ha −1 and biochar produced at temperatures lower than 600 °C significantly increased the P availability of agricultural soils. The application of biochar to acid (pH < 6.5) and neutral soils (pH 6.5–7.5) significantly increased plant-P availability by a factor of 5.1 and 2.4, respectively (95% confidence interval 3.5–6.7 and 1.4–3.4, respectively), while there was no significant effect in alkaline soils (pH > 7.5). Taken together, this meta-analysis shows that biochar significantly enhances plant-available P in biochar-amended soils at least for five years.